Detection algorithm for cache pollution attacks based on node state model in content centric networking - Hong-bo TANG; Lin-hao ZHENG; Guo-dong GE; Quan YUAN (Tongxin xuebao)
Aiming at cache pollution attacks in content centric networking,the attacks were quantitatively described by three parameters,namely number of pollution contents,distribution of attack requests and attack intensity,then the cache state model of node under attack was built.Benefited from the analysis of key parameters of cache node,the attack detection principle based on node state model was put forward,correspondingly,two attack detection algorithms were instantiated with the observation parameters of cache replacement ratio and request arrival rate.The simulation results show that proposed algorithm can obtain good detection performance under each decentralized attack and centralized attack.